Comparison of two local discontinuous Galerkin formulations for the subjective surfaces problem - Fried, Michael; Aizinger, Vadym; Bungert, Leon (Computing and Visualization in Science, 2018)
Based on the local discontinuous Galerkin method, two substantially different mixed formulations for the subjective surfaces problem are compared using a number of numerical tests of various types. The work also performs the energy stability analysis for both schemes.
Keywords: Local discontinuous Galerkin method; Image segmentation; Subjective surfaces; Stability analysis; Mixed formulation; Divergence form; Edge detection